2017
DOI: 10.1074/jbc.r117.789537
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis and functions of mammalian iron-sulfur proteins in the regulation of iron homeostasis and pivotal metabolic pathways

Abstract: Fe-S cofactors are composed of iron and inorganic sulfur in various stoichiometries. A complex assembly pathway conducts their initial synthesis and subsequent binding to recipient proteins. In this minireview, we discuss how discovery of the role of the mammalian cytosolic aconitase, known as iron regulatory protein 1 (IRP1), led to the characterization of the function of its Fe-S cluster in sensing and regulating cellular iron homeostasis. Moreover, we present an overview of recent studies that have provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
133
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(138 citation statements)
references
References 99 publications
5
133
0
Order By: Relevance
“…Previously, we confirmed that DMT1 and Fpn1 could be regulated by IRP1 via the IRP/IRE system (10,14,15). IRPs control the expression of several mRNA-encoding proteins of iron metabolism posttranscriptionally (35,36). This posttranscriptional regulation was achieved by the binding of IRPs to IREs in the UTRs of target mRNAs, thus controlling translation or stability of mRNA (37).…”
Section: Discussionsupporting
confidence: 55%
“…Previously, we confirmed that DMT1 and Fpn1 could be regulated by IRP1 via the IRP/IRE system (10,14,15). IRPs control the expression of several mRNA-encoding proteins of iron metabolism posttranscriptionally (35,36). This posttranscriptional regulation was achieved by the binding of IRPs to IREs in the UTRs of target mRNAs, thus controlling translation or stability of mRNA (37).…”
Section: Discussionsupporting
confidence: 55%
“…In eukaryotes, mitochondria are the hotspots for iron utilization-these organelles house heme assembly and the majority of Fe-S cluster biosynthesis apparatus (3,4). Mitochondria contain respiratory complexes which comprise many ironcontaining cofactors.…”
mentioning
confidence: 99%
“…The incorrectly spliced mRNA is translated into a truncated nonfunctioning ISCU protein with 15 novel amino acids followed by a premature stop, which interrupts the structure of the last α‐helix (Kollberg et al., ; Mochel et al., ; Olsson et al., ). The ISCU protein functions as a scaffolding protein in the formation of iron–sulfur (Fe–S) clusters (Agar et al., ; Lill et al., ; Rouault & Maio, ; Rouault & Tong, ). Fe–S clusters are essential cofactors with electron transferring abilities and can be found in a wide range of proteins including complex I, II, and III of the ETC, as well as in mitochondrial aconitase in the TCA cycle (Agar et al., ; Crooks et al., ).…”
Section: Introductionmentioning
confidence: 99%